Investigation of the filtering methods on 3D models using terrestrial laser scanning data - Uzar, Melis; Tunalioglu, Nursu; Arican, Duygu; Arda, Tumay (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
Making inventories of cultural heritages is the most important issue for protecting and transferring of these historical artefacts from past to the future. Creation of these inventories is quite crucial for restoration of worn artefacts and recovering artefacts, which have lost attributes over time, with collected data. During the creation of these inventories, documentation of these artefacts should be done without damaging them. Laser scanning measurement system has been widely used in the documentation of cultural heritage with the use of state-ofart-technology in this field. Laser scanning is a technology that can collect three-dimensional location data quickly, reliable and detailed for many different applications. Today, laser scanners are an important research topic in especially photogrammetry and remote sensing study areas. In this study, modeling facilities have been exposed with terrestrial laser scanner technology to make three dimensional inventories of historic artefacts. In this context, the filtering effects on the models have been investigated. For this purpose, two different datasets collected with different scanners has been used. The first dataset belongs to Church of Tavra Creek, which is located in Sivas Temeltepe. Second dataset is a point cloud which belongs to stone building in Mersin. Within the scope of this study, coloring point cloud, registration, filtering, surface modeling, and deviation analysis have been performed on data sets, respectively. Noise reduction and smoothing filters have been used to filter data. Comparisons of the obtained models have been utilized by deviation analysis. Accordingly, the effects of filtering methods on the creation of historical inventories have been examined.
Keywords: Terrestrial Laser scanning; architectural inventory; filtering methods; point cloud; 3D modeling; RECONSTRUCTION; DOCUMENTATION; BEHAVIOR; Engineering